FXYD1 negatively regulates Na+/K+-ATPase activity in lung alveolar epithelial cells - Wujak, Łukasz A.; Blume, Anna; Baloğlu, Emel; Wygrecka, Małgorzata; Wygowski, Jegor; Herold, Susanne; Mayer, Konstantin; Vadász, István; Besuch, Petra; Mairbäurl, Heimo; Seeger, Werner; Morty, Rory E. (Respiratory physiology & neurobiology, 2016)
Acute respiratory distress syndrome (ARDS) is clinical syndrome characterized by decreased lung fluid reabsorption, causing alveolar edema. Defective alveolar ion transport undertaken in part by the Na+/K+-ATPase underlies this compromised fluid balance, although the molecular mechanisms at play are not understood. We describe here increased expression of FXYD1, FXYD3 and FXYD5, three regulatory subunits of the Na+/K+-ATPase, in the lungs of ARDS patients. Transforming growth factor (TGF)-β, a pathogenic mediator of ARDS, drove increased FXYD1 expression in A549 human lung alveolar epithelial cells, suggesting that pathogenic TGF-β signaling altered Na+/K+-ATPase activity in affected lungs. Lentivirus-mediated delivery of FXYD1 and FXYD3 allowed for overexpression of both regulatory subunits in polarized H441 cell monolayers on an air/liquid interface. FXYD1 but not FXYD3 overexpression inhibited amphotericin B-sensitive equivalent short-circuit current in Ussing chamber studies. Thus, we speculate that FXYD1 overexpression in ARDS patient lungs may limit Na+/K+-ATPase activity, and contribute to edema persistence.
Gesehen am 30.06.2020
Available online 26 September 2015
Im Titel sind die Plus-Zeichen hochgestellt